Software Defined User Centric 5G Wireless Network Framework - Hua Qu; Zhirong Luan; Jihong Zhao; Xiguang Xu; Tao Zhang (Dianxin kexue)
The radio access network of 5G is a complex heterogeneous network.The independence of different protocols limits the network performance. To unify the management of the heterogeneous network and provide personalized service，a software defined user centric framework was provided. Such framework unifies the management of the heterogeneous network by the idea of software define，and it breaks the concept of traditional ce11.The user centric cell is formulated for each user to provide better service and all the base stations in the cell can serve this user. This framework provides personalized service for each user and improves the peak rate as well as the cell edge rate.